Send the Alabamians : World War I Fighters in the Rainbow Division. - Frazer, Nimrod Thompson (University of Alabama Press, 2014)
Send the Alabamians recounts the story of the 167th Infantry Regiment of the WWI Rainbow Division from their recruitment to their valiant service on the bloody fields of eastern France in the climactic final months of World War I. To mark the centenary of World War I, Send the Alabamians tells the remarkable story of a division of Alabama recruits whose service Douglas MacArthur observed had not "been surpassed in military history." The book borrows its title from a quip by American General Edward H. Plummer who commanded the young men during the inauspicious early da.